Disturbances of Time Measurement in UWB Localization Systems - Comparison of Protective Mechanisms in DW1000 and DW3000 Modules - Jan KOBUSIEWICZ; Krzysztof PLEC; Wojciech MAĆKOWIAK; Michał OZYRA; Slawomir HANCZEWSKI (Communications of International Proceedings, 2025)
This study investigates the application potential of the DW1000 and DW3000 UWB transceiver platforms in the design of high-accuracy indoor positioning systems. As industrial environments increasingly adopt cyber-physical automation, indoor localization technologies are evolving into critical components of intelligent manufacturing and warehouse management infrastructures. Accurate position tracking of mobile platforms—such as autonomous transportation units and robotic systems—is now a fundamental requirement for modern production and logistics environments. Ensuring precise spatial awareness enables robust automation, enhances operational safety, and facilitates data-driven optimization consistent with Industry 4.0 objectives.
Keywords: UWB; indoor positioning systems